Juglone Suppresses Inflammation and Oxidative Stress in Colitis Mice - Chen, Shuai; Wu, Xin; Yu, Zengli (Frontiers in Immunology, 2021)
Juglone (JUG), a natural product found in walnut trees and other plants, shows potent antioxidant, antimicrobial, and immunoregulatory activities. However, it remains unknown whether JUG can alleviate ulcerative colitis. This study aims to explore the effect of JUG on dextran sulfate sodium (DSS)-induced colitis in mice. C57BL6/J mice were divided into three groups : the vehicle group, the DSS group, and the JUG group. The experiments lasted for 17 days, during the experiment, all mice received dimethyl sulfoxide (DMSO, 0.03% v/v)-containing water, while the mice in the JUG group received DMSO-containing water supplemented with JUG (0.04 w/v). Colitis was induced by administering DSS (3% w/v) orally for 10 consecutive days. The results showed that the JUG treatment significantly ameliorated body weight loss and disease activity index and improved the survival probability, colon length, and tissue damage. JUG reversed the DSS-induced up-regulation of pro-inflammatory cytokines, including interleukin (IL)-6, 12, 21, and 23, and tumor necrosis factor-alpha. In addition, anti-inflammatory cytokines, such as IL-10 and transforming growth factor-beta, were both in the serum of the colitis mice. Additionally, the JUG treatment also prevented the DSS-induced activation of mitochondrial uncoupling protein 2 and phospho-Nuclear Factor-kappa B p65 and inhibition of the kelch-like ECH-associated protein 1 and NF-E2-related factor 2. Furthermore, the JUG group possessed a similar microbial community structure as the DSS group, which was dominated by the Lachnospiraceae_NK4A136_group at the genus level and reduced relative abundance of Escherichia Shigella. In conclusion, our results demonstrated that JUG could be a promising agent for UC prevention to regulate inflammatory cytokines and oxidative stress.